ANALISIS EFISIENSI TRANSFORMATOR DISTRIBUSI DI PT. SADHANA - Pratama, Muhammad Arkan Restu; Dhofir, Moch.; Nurwati, Tri (Jurnal Mahasiswa TEUB, 2024)
Currently, electrical energy is one of the main needs in everyday life, so the quality of electrical energy that reaches consumers’ needs to be considered. This is related to the efficiency of the distribution transformer. The analysis methods that can be used to determine the efficiency of the distribution transformer are the transformer loading percentage analysis method, load imbalance analysis, transformer total loss analysis, and transformer efficiency analysis. In this study, the authors collected current data and total power data on 2 distribution transformers at PT Sadhana, Indonesia. The result of this study is that the highest totaltransformer loss value occurs in transformer 1 with a value of 9,62 kW and a load current of 1704,29 A. While the lowest total loss value occurs in transformer 2 with a value of 5,74 kW and a load current of 1151,43 A. The highest transformer efficiency occurs in transformer 2 which is 99,23% with a transformer load percentage of 39,89%. While the lowest transformer efficiency occurs in transformer 1 with a value of 99,12% and a transformer load percentage of 59,14%. From all the analysis results, it is known that the load current is directly proportional to the total loss of the transformer, and the transformer efficiency is at its nominal value when the transformer loading is in the range of 40%-80%. Keywords: Distributing Transformer, Percentage of Loading, Load Imbalance, Transformer Total Losses, Transformer Efficiency.